Analysis Of The Relationship Between Company Culture And Employee Achievement Motivation At PT. United Tractors Tbk - Nur Athirah Hadis; Nurfitriany Fakhri (Journal Of Global Research Publications, 2024)
This research aims to determine the relationship between company culture and employee achievement motivation at PT United Tractors Tbk. This company is known for its good work culture, with the slogan "moving as one" and solution-based company values. The success of this company was achieved with the support of employees who have high abilities, skills and motivation. This research uses qualitative methods with data collection techniques through observation, interviews and literature study. Data were analyzed using triangulation to ensure validity. The research results show that a strong and healthy company culture can increase employee achievement motivation. A company culture that is innovative, supportive and open to evaluation and attention to detail regarding employee needs, such as a safe and comfortable work environment, plays a role in creating creative, committed and motivated employees. PT United Tractors also shows that good company support, continuous employee training and development, as well as a fair and transparent performance appraisal system, can encourage employees to achieve higher achievements. These findings support the hypothesis that there is a positive relationship between corporate culture and employee achievement motivation, that the stronger the company culture, the higher the employee achievement motivation.